IBM BAGI WIRAUSAHA MUDA - Wahyuni, Endang Dwi (Studi Kasus Inovasi Ekonomi, 2016)
IbM to be performed aims to help partners in theproduction and marketing of business partners.Another goal is to help partners to improvecompetitiveness, so that the company'scompetitiveness can be improved, it needs someimprovement and development to be done bypartners, such as fixing the production process,product design and the addition of media onlinemarketing with others and collaborate with otherparties. This is because the company'scompetitors are already using more advancedtechnology, while the partners are still usingsimple technology (manual). so the quality of theproduct is less good and less attractive. In orderto increase competitiveness and sales, thecompany needs to improve its product design andthe use of digital printing in the screen printingproducts (T-shirts). RGB Merch partnercompany that is a company that produces a kindshirt distro, where a machine or equipment usedis still simple. While com-petitors are alreadyusing advanced techno-logies.For businessdevelopment and to en-hance competitiveness,the company partners should immediately use amore sophisticated production equipment so thatproduct quality could be better. In addition theuse of sophis-ticated equipment can producemore output so that the production cost can bereduced. On-line shop to expand the networkusing a variety of existing social networking,such as face-book, nice shops, and others. It isalso Eny Suprapti Fakultas Ekonomi Dan Bisnis UMMnecessary to make cooperation with varioussuppliers of goods, so as to increase thecompleteness of goods sold. After the serviceteam provides assistance and businessconsulting. Companies partner to makeimprovements, both in the production andmarketing process, so that partner companiescan increase the number and quality of products,and the production cost can be reduced. Inaddition, partner com-+panies can expandmarketing network, and collaborating withsuppliers, so that products sold more varied andcan be more known to the public, increasingsales and profits also increased.